A Rare Case of Chemical Peritonitis Following Intravesical Botulinum A Injection for Detusor Overactivity - Samantha Crowther; Subhash Garikipati; Anu Bondili (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
A 72 year old lady attended for elective administration of intravesical Botulinum A toxin (Botox 200iu) injections, as a daycase procedure, for the treatment of detrusor over activity. The procedure was undertaking without any complications. A few hours after the operation the patient developed severe constant generalized abdominal pain and distension. There were no other associated features. She underwent a computerized tomography (CT) scan of her abdomen and pelvis which was normal, followed by a Cystogram which was also normal. The only abnormal finding was that of an elevated CRP (380 mg/L). She was treated empirically with intravenous Cefuroxime and Metronidazole for twenty-four hours. Her symptoms slowly resolved and she was discharged home on the 3rd post-operative day with oral antibiotics. She experienced no further complications. Although the exact cause of her symptoms was not found, the timing of this complication means it is highly probable to be due to the intravesical Botox injection. Given the above findings, the most likely diagnosis is that chemical peritonitis. This has not previously been reported in the literature as a side effect of intravesical Botox.